2018
DOI: 10.1093/ejcts/ezy339
|View full text |Cite
|
Sign up to set email alerts
|

Aortic morphological variability in patients with bicuspid aortic valve and aortic coarctation

Abstract: OBJECTIVES This study aimed to explore aortic morphology and the associations between morphological features and cardiovascular function in a population of patients with bicuspid aortic valve, while further assessing differences between patients with repaired coarctation, patients with unrepaired coarctation and patients without coarctation. METHODS This is a single-centre retrospective study that included patients with available cardiovascular magnetic resonance imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 32 publications
0
37
1
1
Order By: Relevance
“…Our previous cross-sectional study focused exclusively on aortic morphology suggested that patients with reCoA tended to present increased aortic diameters compared with CoA patients with successful repair and no residual narrowing,18 yet current results did not reveal an association between reCoA and aortic growth rate. This may be partly due to a relatively short time window, nevertheless significant increases in aortic size were observed in other patients over this time.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Our previous cross-sectional study focused exclusively on aortic morphology suggested that patients with reCoA tended to present increased aortic diameters compared with CoA patients with successful repair and no residual narrowing,18 yet current results did not reveal an association between reCoA and aortic growth rate. This may be partly due to a relatively short time window, nevertheless significant increases in aortic size were observed in other patients over this time.…”
Section: Discussioncontrasting
confidence: 77%
“…Results showed that patients with repaired CoA tended to have slower aortic root growth rate compared with patients with isolated BAV. Previous work from our group based on a statistical shape modelling framework18 revealed nuanced differences in arch morphology in BAV patients with/without CoA, suggesting detrimental functional implications for some aortic arch architectures, and with BAV+CoA patients generally presenting with smaller ascending and larger descending aortas compared with isolated BAV. This agrees with observations in the literature that prior CoA repair may protect BAV aorta from rapid dilation 8.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…22 Altered aortic geometry may be an additional differing feature, as previous CoA repair is associated with a 'gothic' aortic arch. 23 Mechanobiological studies on the aortic valve have elucidated the intricate relationship between altered leaflet pressure, stretch and shear stresses and the cellular, proteomic and genomic profiles of aortic valves which may be involved in aortic valve dysfunction. 24 These abnormalities in aortic and aortic valve mechanics, therefore, may potentially contribute to the accelerated valvular dysfunction that we observed in the patients with BAV-CoA.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…Traditionally, treatment of aortic arch pathology was a domain of cardiac surgery. [1][2][3][4][5][6] The advent of transcatheter procedures, along with improvement in equipment, has opened a new field enabling therapy in patients with native or previously repaired coarctation. [7][8][9][10] Percutaneous techniques, such as, balloon dilation and stenting, allow clinicians to safely decrease or abolish most gradients along the aorta, albeit with limitations.…”
Section: Introductionmentioning
confidence: 99%